Effectiveness of education intervention programme on life support measures for the nurses working in emergency unit of BPKIHS: a pre-experimental study - Yadav, Upendra; Mehta, RS (Journal of BP Koirala Institute of Health Sciences, 2018)
Introduction: Lack of resuscitation skills of nurses in basic life support (BLS) and advanced life support (ALS) has been identified as a contributing factor to poor outcomes of cardiac arrest victims.Objective: To assess the effectiveness of education intervention programme to improve the knowledge of, and thereby the quality of Emergency service; especially in the area of Basic Life Support, Advance Life Support and Triage system.Method: Pre-experimental research design was used to conduct the study among the nurses working in Emergency units of B. P. Koirala Institute of Health Sciences where CPR is very commonly performed. Using convenient sampling technique, a total of 24 nurses agreed to participate and to give consent were included in the study. The theoretical, demonstration and re-demonstration sessions were arranged, involving the trained doctors and nurses during the three hours educational programme. Post-test was carried out after education intervention programme. The 2010 BLS and ALS guidelines were used as guide for the study contents. The collected data were analyzed using SPSS-15 software.Result: It was found that there is significant increase in knowledge after education intervention in the components of life support measures (BLS/ALS) i.e. ratio of chest compression to ventilation in BLS (P= 0.001), correct sequence of CPR (p< 0.001), rate of chest compression in ALS (P= 0.001), the depth of chest compression in adult CPR (p< 0.001), and position of chest compression in CPR (P= 0.016). The participating nurses well appreciated the programme and requested to continue in future for all the nurses.Conclusion: The workshop certainly improves the knowledge of the working nurses, and thereby the quality of Emergency service; especially in the areas of Basic Life Support, Advance Life Support and Triage System.Journal of BP Koirala Institute of Health Sciences, Vol. 1, No. 1, 2018, page: 14-19